The lives of working class academics : getting ideas above your station - Burnell Reilly, Iona (Emerald Publishing, 2023)
A collection of autoethnographies written by academics who self-define as being from a working class heritage. Each one is an account of their lives, their experiences, and their journeys into becoming a higher education professional, in an industry still steeped in elitism.